Immunogenicity of a Third Scheduled Dose of Rotarix in Australian Indigenous Infants: A Phase IV, Double-blind, Randomized, Placebo-Controlled Clinical Trial . (4th February 2022) - Middleton, Bianca F; Danchin, Margie; Jones, Mark A; Leach, Amanda J; Cunliffe, Nigel; Kirkwood, Carl D; Carapetis, Jonathan; Gallagher, Sarah; Kirkham, Lea-Ann; Granland, Caitlyn; McNeal, Monica; Marsh, Julie A; et al.
Abstract: Background: Rotarix (GlaxoSmithKline) oral rotavirus vaccine is licensed as 2 doses in the first 6 months of life. In settings with high child mortality rates, clinical protection conferred by 2 doses of Rotarix is reduced. We assessed vaccine immune response when an additional dose of Rotarix was given to Australian Aboriginal children 6 to <12 months old. Methods: ORVAC is a 2-stage, double-blind, randomized, placebo-controlled trial. Australian Aboriginal children 6 to <12 months old who had received 1 or 2 prior doses of Rotarix rotavirus vaccine were randomized 1:1 to receive an additional dose of Rotarix or matched placebo. The primary immunological end point was seroresponse defined as an anti-rotavirus immunoglobulin A level ≥20 AU/mL, 28–56 days after the additional dose of Rotarix or placebo. Results: Between March 2018 and August 2020, a total of 253 infants were enrolled. Of these, 178 infants (70%) had analyzable serological results after follow-up; 89 were randomized to receive Rotarix, and 89 to receive placebo. The proportion with seroresponse was 85% after Rotarix compared with 72% after placebo. There were no occurrences of intussusception or any serious adverse events. Conclusions: An additional dose of Rotarix administered to Australian Aboriginal infants 6 to <12 months old increased the proportion with a vaccine seroresponse. Clinical Trials Registration: NCT02941107. Abstract : We randomized Australian Aboriginal infants 6 to ≤12 months old to receive 3 versus 2 doses of Rotarix rotavirus vaccine. A third dose increased the proportion with vaccine seroresponse.